Influence of different levels of energy and protein on muscle protein content of broilers reared in environmentally controlled and open sided housing system: Influence of different levels of energy and protein on muscle protein content of broilers reared in environmentally controlled and open sided housing system - Rajendran, K; Mani, K; Shamsudeen, P; Natarajan, A (Indian Journal of Veterinary and Animal Sciences Research, 2025)
An experiment was conducted by feeding diets with different levels of energy (2850, 2950 and 3050 kcal/kg in pre-starter diet, 2950, 3050 and 3150 kcal/kg in starter dietand 3050, 3150 and 3250 kcal/kg in finisher diet) and protein (21.5, 22.5 and 23.5% inpre-starter diet, 20.5, 21.5 and 22.5% in starter diet and 19, 20 and 21% in finisher diet) to commercial broilers for a period of five weeksto assess the muscle protein content in environmentally controlled and open sided housing system. The interaction between feeding different levels of energy and protein and housing system revealed no significant influence on breast and thigh muscle protein level in broilers.